Investıgation of The Effects of Organizational Cynicism on Organizational Citizenship Behavior in Forest Products Enterprises: The Example of Trabzon - Ersen, Nadir; Karayiğit, Öner; Akyüz, İlker; Bayram, Bahadir Cagri (Bartın Üniversitesi, 2021)
In this study, organizational cynicism attitudes and organizational citizenship behavior levels of employees in the timber and furniture sector in Trabzon; whether there is a significant relationship between organizational cynicism sub-dimensions and organizational citizenship behavior dimension and sub-dimensions; and organizational cynicism sub-dimensions on organizational citizenship and its sub-dimensions were tried to be determined. The population of the research consists of the employees in the enterprises operating in the forest products sector in the province of Trabzon. Within the scope of the study, 315 employees were reached. 305 questionnaires were evaluated. As a method, face-to-face survey method was generally used. As a result of the study, the mean score of the dimensions of organizational cynicism was low and the dimension of organizational citizenship behavior was moderate. A weak and negative relationship was found between the organizational cynicism attitudes of the employees within the scope of the research and organizational citizenship behavior. Organizational cynicism has a negative effect on organizational citizenship behavior.

Bu çalışmada, Trabzon'da kereste ve mobilya sektöründe çalışanların örgütsel sinizm tutumları ve örgütsel vatandaşlık davranış sergileme düzeyleri; örgütsel sinizm alt boyutları ile örgütsel vatandaşlık davranış boyutu ve alt boyutları arasında anlamlı bir ilişkinin olup olmadığı; ve örgütsel sinizm alt boyutlarının örgütsel vatandaşlık ve alt boyutlarına etkisi belirlenmeye çalışılmıştır. Araştırma evrenini, Trabzon ilinde orman ürünleri sektöründe faaliyet gösteren işletmelerdeki çalışanlar oluşturmaktadır. Çalışma kapsamında 315 çalışana ulaşılmıştır. 305 anket değerlendirmeye alınmıştır. Yöntem olarak genellikle yüz yüze anket yöntemi kullanılmıştır. Çalışma sonucunda, örgütsel sinizm boyutlarının puan ortalaması düşük ve örgütsel vatandaşlık davranışı boyutu orta düzeyde çıkmıştır. Araştırma kapsamındaki çalışanların örgütsel sinizm tutumları ile örgütsel vatandaşlık davranışı arasında zayıf düzeyde ve negatif yönlü bir ilişki bulunmuştur. Örgütsel sinizm örgütsel vatandaşlık davranışı üzerinde negatif yönde etkiye sahiptir.
Orman Ürünleri İşletmelerinde Örgütsel Sinizmin Örgütsel Vatandaşlık Davranışı Üzerine Etkisinin Araştırılması: Trabzon Örneği
Keywords: Timber; Pulp and Paper; Kereste; Hamur ve Kağıt